UPACARA KORBAN DALAM TRADISI MAYU DESA, TRADISI MEGALITIK TENGGER (STUDI ETNOARKEOLOGI) - Hari Lelono (BRIN, 2014)
The tribe of Tengger, who lives in the surrounding of Mount Bromo - East java, is one of the tribes that still upholding the ancestral tradition. i.e. honoring the spirits of the ancestor. The question arises from this subject is what religious background that actually reflected through their daily activities, Hindu or Indonesia indigenous (Jawa)? The mystery revealed in one of the important rituals that only been held once every five years, the mayu desa ritual. Such ritual is also the main discussion of this article. An ethno-archeological approach was chosen to gain data and information because there are several menhirs and punden found on site and many ethnographical data still available to be observed. In this regards, a method consisted of observation and in-depth interview with whoever that considered would be able to provide information was applied. Through an analysis on a series of data, it is concluded that the animal offerings (a cow or a bull in ancient time) in the sacrificial ritual mayu desa is the central ritual in conducting the tradition of honoring the world of the spirits of the ancestor in each village of Tengger.